СВЯЗЬ ЭНДОГЕННОЙ ИНТОКСИКАЦИИ С НАРУШЕНИЕМ ФУНКЦИОНАЛЬНО-МЕТАБОЛИЧЕСКИХ ПАРАМЕТРОВ ПЕЧЕНИ У БОЛЬНЫХ С ХРОНИЧЕСКИМ ЛЕЙКОЗОМ (Journal of Science-Innovative Research in Uzbekistan, 2025)
In patients with hemoblastoses the combination of tumor intoxication and massive cytotoxic therapy causes the development of endogenous intoxication and massive cytotoxic therapy causes the development of endogenous intoxication and worsening of treatment  outcomes.